APPRAISAL SYSTEM IN NEWS ITEM - Widiastuti, Noor (LANTERN (Journal on English Language, Culture and Literature), 2015)
This thesis relates to appraisal system in news item. It is aimed at describing evaluative language used by journalists. Two news items from the different source exposing the sametopic, that is, the world‟s reaction on Hashimoto‟s comments dealing with the justification ofsex slavery practice by Japanese soldiers in World War II, are analysed based on attitude,amplification and source aspects. It is qualitative research. The method of collecting dataapplied is non-participant observation since the researcher is not involved in producingutterances being studied. Referential identity method is applied in analyzing. The resultshows that negative attitude and amplification are dominant. In addition, the assessments insource aspect are predominated by that of from other than the journalists. Moreover, themodality coming from other than the journalists they are careful in giving additional voice.On the contrary, the presence of concession indicates additional voice of the journalists. Key words: Systemic Functional Grammar, appraisal system, news item